The role of maltodextrin in iron nanoparticle formulations for food fortification and pharmaceutical applications: A scoping review - Rizki Ananda; Dono Indarto; Yuliana Heri Suselo (Indonesian Nutrition Association, 2026)
Background: Iron nanoparticle formulation is an innovative approach to enhance the stability and bioavailability of iron, which is crucial in addressing global iron deficiency. However, conventional iron supplementation strategies, like oral ferrous sulfate, face limitations in absorption and bioavailability. Specifically, dietary inhibitors and gastrointestinal conditions can impede iron uptake. Moreover, oral iron supplements often cause side effects such as nausea, constipation, and abdominal discomfort, affecting patient compliance. These challenges highlight the need for innovative approaches to enhance iron delivery. In this context, nanotechnology offers a promising solution to conventional iron supplementation limitations. Iron nanoparticles provide improved solubility, targeted delivery, and controlled release, thereby enhancing therapeutic effectiveness. Both in vitro and in vivo bioavailability studies have demonstrated that nanoparticle-based formulations improve iron absorption and reduce side effects. By improving iron absorption and reducing side effects, nanoparticle-based formulations represent a significant advancement in IDA management. Maltodextrin, a water-soluble and neutral starch-derived polysaccharide, serves as an effective encapsulating agent in nanoparticle formulation, enhancing stability, solubility, and controlled release, thereby overcoming limitations of traditional iron supplementation. Both in vitro and in vivo studies have demonstrated the potential of maltodextrin-based iron nanoparticles to improve bioavailability and therapeutic outcomes. Objective: This scoping review aims to explore the role of maltodextrin in iron nanoparticle formulations based on the latest scientific evidence. Methods : A systematic literature search was conducted across four databases: PubMed, ScienceDirect, Scopus, and SpringerLink, using structured keywords. Inclusion criteria consisted of original English language articles published between 2019 and 2024 that discussed the use of maltodextrin in iron nanoparticle systems. Exclusion criteria The selection and data synthesis process followed PRISMA-ScR guidelines. Results : Out of 8620 articles identified, three met the inclusion criteria: Arazo-Rusindo et al. (2023), Kumari et al. (2023), and Baldelli et al. (2023). These studies demonstrated that maltodextrin acts as a carrier, stabilizer, and bioavailability enhancer, while also improving encapsulation efficiency and nanoparticle stability. Conclusions : These findings highlight the potential of maltodextrin in developing functional food products and pharmaceutical formulations based on iron nanoparticles; however, further research is needed to optimize formulations and evaluate long-term safety.